IGF1 Gene Therapy Modifies Microglia in the Striatum of Senile Rats - Falomir-Lockhart, Eugenia; Dolcetti, Franco Juan Cruz; García-Segura, Luis Miguel; Hereñú, Claudia Beatriz; Bellini, Maria Jose (Frontiers in Aging Neuroscience, 2019)
Microglial cells become senescent with aging; this phenotypic alteration contributes to basal central nervous system neuroinflammation being a risk factor for age related neurodegenerative diseases. In previous studies we have observed that Insulin like growth factor 1(IGF1) gene therapy is a feasible approach to target brain cells, and that is effective to modify inflammatory response in vitro and to ameliorate cognitive or motor deficits in vivo. Based on these findings, the main aim of the present study is to investigate the effect of IGF1 gene therapy on microglia distribution and morphology in the senile rat. We found that IGF1 therapy leads to a region-specific modification of aged microglia population.